High Expression of Tumor Abnormal Protein Preoperatively Predicts Poor Prognosis of Patients With Esophageal Squamous Cell Carcinoma - Cheng, Yuanjun; Fang, Qianru; Chen, Yongbing; Zang, Guohui; Yao, Jie (Frontiers in Surgery, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) acts as a fatal malignant tumor among human beings and is marked by late-stage diagnosis, frequent recurrence, metastasis, and therapy resistance. Tumor abnormal protein (TAP) remarkably affects cancer development and progression of human cancers. TAP has been shown to be a biomarker for gastric and lung cancer progression. Nevertheless, the clinical value exhibited by TAP for ESCC has not been well-explained in the current literature. Methods: The present study included 183 ESCC cases who received surgical resection and 183 cases who had normal physical checkup from March 2013 to January 2015 at the People's Hospital of Chizhou, and used the TAP detection agent for evaluating the TAP relative level. Results: As found, ESCC patients presented an obviously higher TAP expression relative to cases who had normal physical checkup. Moreover, TAP expression was significantly downregulated after surgery. Furthermore, the TAP expression was correlated with gender, smoking, pathologic differentiation, and pN stage, but not with age, tumor location, surgical type, pT stage, and vascular invasion. High expression of TAP was significantly correlated with poorer overall survival (OS) rate in ESCC patients. TAP was an independent prognostic predictor in ESCC patients, based on the multivariate survival analysis. Conclusion: The study reveals how TAP upregulation promotes ESCC malignant progression, and concludes that TAP acts as the therapeutic target and potential biomarker specific to ESCC.